Add <math><mstyle displaystyle="true"><mn>18</mn></mstyle></math> to both sides of the inequality.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>18</mn></mstyle></math> .

Multiply both sides by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify the right side.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

The result can be shown in multiple forms.

Inequality Form:

Interval Notation:

Do you know how to Solve the Inequality for k -18+k/3<=-26? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.